Pengukuran dan Evaluasi Maturity Level Tata Kelola Teknologi Informasi pada PT Romi Violeta menggunakan Framework Cobit 2019 - Virasari, Cantika Anisya; Nasrullah, Muhammad; Kusumawati, Aris (Innovative: Journal Of Social Science Research, 2024)
PT Romi Violeta is one of the largest furniture manufacturing and exporting companies in Indonesia, producing wooden and woven indoor furniture. Although the company has implemented information technology to support its operations, there has not yet been a thorough assessment of its IT governance. Inadequate governance has led to issues such as miscommunication, production errors, and delays in product delivery, negatively impacting sales. This research aims to measure and evaluate the maturity level of IT governance using the COBIT 2019 framework. A descriptive qualitative method is employed through observations and direct interviews with stakeholders. The focus of the study includes the BAI06, BAI09, BAI10, and DSS04 domains. The findings indicate a need to improve the management of changes, assets, configurations, and business continuity. Recommendations include implementing a structured change plan, enhancing asset protection, and developing business continuity strategies. Implementing these recommendations can enhance the maturity level of IT governance and align IT with the company’s business objectives.